LncRNA PCED1B‐AS1 activates the proliferation and restricts the apoptosis of glioma through cooperating with miR‐194‐5p/PCED1B axis. Issue 2 (3rd November 2019) - Yang, Jinghui; Yu, Duo; Liu, Xueshibojie; Changyong, E.; Yu, Shan
Abstract: Glioma with poor prognosis is accepted as a lethal, malignant intracranial tumor among central nervous system diseases. It has been frequently exhibited that long noncoding RNAs (lncRNAs) exert indispensable functions in glioma through regulating gene expression through various molecular mechanisms. To unveil a novel lncRNA functioning in glioma, we browsed the cancer genome atlas dataset and chose the lncRNA PC‐esterase domain containing 1B antisense RNA 1 (PCED1B‐AS1) for further investigations. Loss‐of‐function experiments depicted that the proliferation ability was restrained and apoptosis ability was induced in glioma cells by PCED1B‐AS1 silencing and this phenomenon was also observed when PCED1B was knocked down. In view of the position of PCED1B‐AS1 in the cytoplasm, we produced the Venn diagram and discovered one shared microRNA of PCED1B‐AS1 and PCED1B. The competing endogenous RNA network formed by PCED1B‐AS1, miR‐194‐5p, and PCED1B was attested by mechanism assays. Rescue experiments reconfirmed that miR‐194‐5p suppression or PCED1B overexpression neutralized the obstructive impacts of PCED1B‐AS1 silence on proliferation and the promoting effects of PCED1B‐AS1 silence on apoptosis. The modulation mechanism of the PCED1B‐AS1/miR‐194‐5p/PCED1B axis in glioma was investigated and affirmed, which supports researchers with a new insight into the therapy of patients with glioma. Abstract : 1. Both PCED1B‐AS1 and PCED1B are high‐expressed in glioma. 2. PCED1B‐AS1 or PCED1B silence inhibits the proliferation and enhances the apoptosis.